GRI 301-306 Environmental Disclosures and SDG Reporting Quality among Indonesian Property Companies - Riani Sukma Wijaya; Sharul Effendi Bin Janudin; Nor Hanani Binti Ahamad Rapani (Ilomata International Journal of Tax and Accounting, 2026)
This study investigates how corporate social responsibility (CSR) disclosure contributes to the environmental dimension of the Sustainable Development Goals (SDGs). The analysis uses a quantitative design and relies on secondary data obtained from the Indonesia Stock Exchange, company websites, annual reports, and sustainability reports. The sample consists of 82 property companies listed during the 2020–2024 period, resulting in 410 firm-year observations. Panel data regression analysis is applied to evaluate the relationship between environmental CSR disclosure and SDG reporting quality. The findings indicate that environmental disclosures influence SDG reporting quality differently. Energy disclosure and water disclosure have positive and statistically significant effects, with water disclosure showing the strongest effect. Material disclosure has a negative and statistically significant relationship with SDG reporting quality. In contrast, biodiversity, emissions, and waste disclosures do not show statistically significant effects. Overall, these findings suggest that SDG reporting quality in Indonesian property companies is more closely associated with substantive and measurable environmental practices related to energy efficiency and water management. The results also confirm that environmental CSR disclosure should not be treated as a single aggregate construct, because each GRI 301–306 dimension has different explanatory power in relation to SDG reporting quality.